Tests with recording traction dynamometer determine pull of different loads on roads of different grades and surfaces - Richards, James C.; Sorgatz, Frank (My University, 1907)
Introduction: The object in these tests was to determine the pull of certain loads on dry and muddy roads of different grades and surfaces. The following roads were selected on which the tests were to be made; the road that leads from shops to East college entrance oiled road (Manhattan Avenue) from East college entrance to Fremont street; Fremont street from South end of oiled road to 9th street; South on 9th street to Leavenworth street; East on Leavenworth street to 2nd street; South on 2nd street to Humbolt street; West on Humbolt street to 9th street; North on 9th street to Fremont street; East on Fremont street to 2nd street; North on 2nd street to Moro street, West on Moro street to oiled road (Manhattan Avenue); North on oiled road to North end; West from North end of oiled road to gate just North of college barns; from this gate up to shop to starting point. These were supposed to be fair samples of different kinds of road, A survey was then made of these roads and a profile of them plotted on standard profile paper to a convenient scale from which the grades of the road may be obtained. The recording traction dynamometer used in connection with these tests was built in the Kansas State Agricultural College shops, A full description with detail and assembly drawings of the instrument is given in the designers' thesis. A few minro changes were made in the construction of the dynamometer and some new parts were added. The main axle was shortened so that the wheels would track with a farm wagon. The spring that was to be placed in the supply drum was omitted and a brake shoe was substituted in its place. Instead of using one edge of the paper as a zero line, a marker was attached to the machine to make a zero or base line and in which the movable pencil would lie when there was no pull. As metallic coated paper was used on the dynamometer, brass points were substituted in place of the common pencil points.
Citation: Richards, James C. and Sorgatz, Frank. Tests with recording traction dynamometer determine pull of different loads on roads of different grades and surfaces. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Traction Dynamometer; Road Surface Testing; Physics; Applying Loads; Theses